751 Improving Engagement with Home-Based Surgical Skills Simulation. (12th October 2021) - Falconer, R; Semple, C; Cleland, J; Walker, K; Watson, A
Abstract: Introduction: Surgical simulation has been repeatedly shown to facilitate technical skill acquisition. However, trainee engagement with self-directed practice remains variable, despite access to resources. Understanding the motivators and barriers to participation is crucial to develop modules which can effectively meet the learning needs of current, and future, surgical trainees. The aim of this qualitative study was to examine factors which influence trainee engagement with home-based surgical skills simulation. Method: A series of one-to-one semi-structured interviews were conducted remotely with ST3 vascular trainees who had previously consented to take part in a national programme of home-based technical skills simulation. Interview data was transcribed and thematically analysed. Results: 12 trainees were interviewed during a 4-week period. Overall, trainees valued simulation but found it difficult to balance against clinical commitments and mandatory training requirements, particularly if there were limited opportunities for skill transfer to the real-world environment. Although simulation was acknowledged to be a safe environment for experiential learning, trainees alluded to an underlying culture of perfection which limited willingness to learn from mistakes, even within a simulated setting. In addition, traditional attitudes about the apprenticeship model of surgical training prevail, with simulation often viewed as inferior to learning "on the job" in theatre. Conclusions: Trainee engagement with home-based surgical skills simulation may be influenced by a range of systemic factors. In future, formal certification of simulation modules, mandating simulated competencies and curricular integration may help improve participation, as well as supporting cultural shift towards recognition of simulation as a vital component of modern surgical training.